The Regulation on Sexual Harassment in ASEAN Workers: Evidence from Several Countries - Taufiqurrohman, Ahmad Asari; Wibowo , Dwi Edi; Victoria, Ong (Journal of Human Rights, Culture and Legal System, 2024)
Despite the existence of numerous laws and regulations that govern policy arrangements for the management of sexual harassment cases, victims still lack access to justice. This research examines the rules governing the management of sexual harassment cases in the workplace, with a particular emphasis on ASEAN member countries. This research employs normative juridical methods, which include statutory, conceptual, and comparative approaches. The research results show that, despite the existence of the 1955 Employment Law and Criminal Code in Malaysia, the incidence of sexual harassment continues to rise. To address this issue, it is critical to involve all employees in the development, execution, and oversight of workplace policies. Second, Singapore's primary law for dealing with sexual harassment, the Protection from Harassment Act, is accompanied by an employment law. Nevertheless, there are apprehensions regarding the inadequate remedies, uncertainty, and statutory protections against harassment, particularly in the workplace. Third, Indonesia has implemented numerous laws and regulations to manage sexual harassment cases. However, the government still faces challenges, such as an incomplete and insufficient legal framework, which results in victims being denied justice. Fourth, the effective implementation and protection of women's rights necessitate a comprehensive approach that considers cultural sensitivities, regional dynamics, and international norms to reconstruct sexual harassment regulations in ASEAN countries. As a result, it is critical to establish an anti-sexual harassment organizational culture and restructure sexual harassment regulations to protect victims' rights.